Cinema direto na Paraíba: a consolidação de um estilo na representação do real - Souza, Leandro Cunha de (2017)
In this research, we seek to comprehend how occurs the arrival and difusion of an approach mode of the real, the so called direct cinema, with its sound record stylistic synchronous to the image, on the documentary from Paraiba, from the late 70s. This style stood out for giving people voice so they could talk about themselves to the cinema, revealing, this way, a language sensitive to the social matters, to the political problems, to the gender and identity matters, beside the many cultural manifestations. We discussed the role of UFPB's Cinematographic Documentation Core (NUDOC) as a formation agent of new directors, from the exchange with Paris Varan Association (Ateliers Varan), promoting internships in direct cinema in João Pessoa and Paris, thus providing a technical, cultural and theorical baggage consistents to the new directors. On the scope of our research, we conceptualized, initially, the documentary against its stylistic ways and delimitations of a representation field. Right next, we discussed the direct cinema, its approaching strategies of the real and its precursors in Paraiba, the consolidation of a style (the expositive mode on the paraibano documentary), NUDOC's role on the difusion of the direct and finally the stylistic of the direct in Paraiba: from the 80s until nowadays. For this, we based our analysis on the main theories of the documentary study, on the productions study about the Super-8 mm and the direct cinema made in Paraiba, on the interviews and notes produced along the research, discussing the language, the technology, the stylistic resources used in its historical context. These productions contribute with the identity formation of the local cinema, influencing new generations of directors. Lastly, we will demonstrate our considerations about the stylistic procedures used in the direct e, this way, contribute with a new look about the study of the audio-visual narratives apllied to the making of the documentary in Paraiba.